2021
DOI: 10.1016/j.amjsurg.2020.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of complicated appendicitis during COVID-19 pandemic

Abstract: Background: The novel coronavirus (COVID-19) strain has resulted in restrictions potentially impacting patients presenting with acute appendicitis and their disease burden. Methods: All acute appendicitis admissions (281 patients) between 1/1/2018-4/30/2020 were reviewed. Two groups were created: 6 weeks before (Group A) and 6 weeks after (Group B) the date elective surgeries were postponed in Massachusetts for COVID-19. Acute appendicitis incidence and disease characteristics were compared between the groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
137
11
16

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(184 citation statements)
references
References 12 publications
20
137
11
16
Order By: Relevance
“…The most likely reason for the findings by Anteby and colleagues is a delay in arrival at the emergency department [2] . This corresponds to studies reporting significant increase in perforated and gangrenous appendicitis due to delay in seeking care during the COVID-19 pandemic [ 3 , 4 ].…”
supporting
confidence: 69%
“…The most likely reason for the findings by Anteby and colleagues is a delay in arrival at the emergency department [2] . This corresponds to studies reporting significant increase in perforated and gangrenous appendicitis due to delay in seeking care during the COVID-19 pandemic [ 3 , 4 ].…”
supporting
confidence: 69%
“…One inpatient survey suggested that greater than one-third of parents delayed seeking medical care for their child because of fears surrounding COVID-19, 46 and case series have reported delayed presentations leading to harm. 47 , 48 Similarly, although admissions for repair of atrial septal defects or later-stage repairs of hypoplastic left heart syndrome may safely be deferred for a short period, it is unclear whether reductions in admission rates represent purely elective surgical delays or the possibility of decreased recognition of congenital heart disease because of decreased contact with health care; small case series of increases in sudden death in adults with congenital heart disease without contact with health care institutions during the COVID-19 pandemic have been reported. 49 Taken together, these findings are worrisome, although not definitive, in that unmet health care needs may be accumulating in the pediatric population as a result of decreased health care interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to patients' personal fear of contracting COVID19, they were being advised by primary care physicians, the media, and even healthcare systems to avoid public places, including the emergency department (ED) [ 3 ]. Many patients suffering from symptoms of chest pain, shortness breath, or weakness, for which people typically come to the ED and that are potential indicators of serious conditions, not necessarily associated with COVID19, did not seek medical care [ 4 , 5 ]. Starting in March, some patients who called 911 and required advanced life support (ALS) may have been more critically ill than they would have been before COVID19.…”
Section: Introductionmentioning
confidence: 99%